2013
DOI: 10.3892/ijo.2013.1950
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of schedule-dependent metronomic S-1 chemotherapy in human oral squamous cell carcinoma cells

Abstract: Metronomic chemotherapy is based on administration of anticancer agents at low-doses at close regular intervals with no prolonged breaks, and aims to inhibit vascular endothelial cells as well as tumor cells. Recently, it was suggested that metronomic chemotherapy exerts anti-angiogenic effects by inducing thrombospondin-1 (TSP-1) and early growth response-1 (EGR-1), and antitumor effects by suppressing cancer stem cells. S-1 is a novel orally administered anticancer drug that is a combination of tegafur, 5-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…As a result, we clarified S-1 could exert anti-angiogenic effects via up-regulation of TSP-1. Moreover, we also demonstrated that alternate-day administration of S-1 is more useful than consecutive-day administration in terms of anti-angiogenic effects [58]. Our findings suggested that S-1 might fit with the concept of metronomic chemotherapy in oral cancer treatment [58], [59] (Fig.…”
Section: Investigation Of Mechanisms Of S-1 To Exert Antitumor Effectsupporting
confidence: 55%
See 2 more Smart Citations
“…As a result, we clarified S-1 could exert anti-angiogenic effects via up-regulation of TSP-1. Moreover, we also demonstrated that alternate-day administration of S-1 is more useful than consecutive-day administration in terms of anti-angiogenic effects [58]. Our findings suggested that S-1 might fit with the concept of metronomic chemotherapy in oral cancer treatment [58], [59] (Fig.…”
Section: Investigation Of Mechanisms Of S-1 To Exert Antitumor Effectsupporting
confidence: 55%
“…Moreover, reduction of microvessel density, and induction of TSP-1 expression was markedly seen in alternate days treated tumors than in the four-week treatment and two-week rest, the two-week treatment and one-week rest treated tumors. As alternate days treatment of S-1 could exert remarkable anti-angiogenic effects via up-regulation of TSP-1, we believe S-1 may fit with the concept of metronomic chemotherapy in oral cancer treatment [58] (Fig. 7).…”
Section: Investigation Of S-1 Regimenmentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, the results of the current in vivo experiments suggested that the anti-angiogenic action of bevacizumab and the antitumor effect of S-1 synergistically inhibited tumor cell proliferation and promoted apoptosis. Although VEGF-A expression was not analyzed in mice tumors, it may be possible that S-1/5-FU downregulated VEGF expression by suppressing NF-κB, which finally resulted in decreased MVD and inhibited angiogenesis ( 8 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…One compound is a 5-fluorouracil (5-FU) prodrug, tegafur. The other two are gimeracil (inhibits the 5-FU degradation) and oteracil (lowers the gastrointestinal toxicity of 5-FU) [85]. In an in vitro study, Ferdous et al first demonstrated that more frequent 5-FU dosing (16h treatment, 8h rest vs. 96h treatment, 48h rest or 48h treatment, 24h rest) did not result in more cytotoxic cell death according to3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H tetrazolium bromide assay.…”
Section: Metronomic Therapy In Ocscc 41 Preclinical Evidencementioning
confidence: 99%